METAFOR DALAM ARSITEKTUR KONTEMPORER: PUISI YANG TERKUBURKAN - Barliana, Muhammad Syaom (TERAS)
Architecture is possibly to create in accordance with physics, technical-structure, and functional or its can use only and no more than. But itâs very naive and simplistic. Human as culture species is hold up to get architecture placing as part of cultural process. If language is not word only, but is accentuation, rhythm, gesture, and other expression also, so architectures its means languages with space and dimension, line and plane, texture and structure, and locally material and context. Architecture to produce cultural creation and expression with emotion and deep passion. Architecture its means metaphor, architecture is poetics. In spite of this, in reality of contemporary or modern architecture, architecture form is fashion only. Architecture is new trend models only that created for every season. So architecture newest is obsession that created from difference and recycle from past time. Because that, on the architecture in Indonesia is ersatz metaphor developed such as analogy of legend city, baroque style, rococo style, Brunelleschi dome or dream other world metaphor (Beverly Hills style, Medieval, Mediterranean, Country style, Japan style, etc) that is not relevant of local context. So architecture brand image such as legend city, flower city, river side city is objective to commercial communication only and not architectural essentially.